Processing of sleep-related stimuli: Differences between good and poor sleepers - Spiegelhalder, K; Kyle, S; Prem, M; Feige, B; Nissen, C; Espie, C; Riemann, D (2009)
Previous work suggests that people with poor sleep quality, especially patients with primary insomnia, show an attentional preference for sleep-related stimuli (sleep-related attentional bias). Studies investigating this effect have generally used standardised reaction time experiments, in which the effects of a large number of sleep-related stimuli were averaged. Here, we analysed the data of two studies in order to investigate the contribution of single sleep-related stimuli (words) to sleep-related attentional bias. Results showed that effect sizes of the stimuli were relatively stable between the two studies. Knowing effect sizes of individual stimuli is important for the construction of future attentional paradigms, as well as providing a better understanding of the magnitude and content of sleep-related attentional bias. © 2009 Springer.